The use of aromatherapy during labor: an integrative review - Fllávia Costa de Asunción, Anna; da Silva Brito, Juliana; Cirilo De Lima Filho, Juscelino; Roberta Sena Luna, Kátia; Zambrano Lins , Katherine; Cecília Domingos de Souza, Maria; Kelly Lauriano Gomes da Silva, Noedja; Rodrigues da Silva Costa, Rosimere (Seven Editora, 2023)
Objective: To describe studies on the use of aromatherapy to relieve pain during labor.  Method: An integrative literature review was carried out in the Nursing Database (BDENF), Medical Literature Analysis and Retrieval System Online (Medline/PubMed), National Institutes of Health (NIH) and  Scientific Electronic Library Online (SciELO).  Available full text, original article, published between 2017 and 2022, available in Portuguese and English and within the theme suggested in the research, and the exclusion  criteria were abstracts published in conference proceedings, in vitro research and other related diseases.  to the thematic axis.  Results: The search and selection of scientific articles was established as follows: 80 publications were found and 103 were excluded for not meeting the previously  defined eligibility criteria, thus leaving 12 publications.  After carefully reading the titles and abstracts, 45 articles were excluded, leaving only 12 complete articles included in this integrative review.  Conclusion: Non-pharmacological methods, such as aromatherapy, have been used to relieve pain, anxiety, stress and other uncomfortable symptoms inherent  to labor. In the analyzed studies, the use of EO during labor had a minimal or null adverse effect for the mother-newborn binomial. DOI: https://doi.org/10.56238/tfisdwv1-095